Mass production of highly-porous graphene for high-performance supercapacitors - Amiri, A.; Shanbedi, M.; Ahmadi, G.; Eshghi, H.; Kazi, S.N.; Chew, B.T.; Savari, M.; Zubir, M.N.M. (Nature Publishing Group, 2016)
This study reports on a facile and economical method for the scalable synthesis of few-layered graphene sheets by the microwave-assisted functionalization. Herein, single-layered and few-layered graphene sheets were produced by dispersion and exfoliation of functionalized graphite in ethylene glycol. Thermal treatment was used to prepare pure graphene without functional groups, and the pure graphene was labeled as thermally-treated graphene (T-GR). The morphological and statistical studies about the distribution of the number of layers showed that more than 90% of the flakes of T-GR had less than two layers and about 84% of T-GR were single-layered. The microwave-assisted exfoliation approach presents us with a possibility for a mass production of graphene at low cost and great potentials in energy storage applications of graphene-based materials. Owing to unique surface chemistry, the T-GR demonstrates an excellent energy storage performance, and the electrochemical capacitance is much higher than that of the other carbon-based nanostructures. The nanoscopic porous morphology of the T-GR-based electrodes made a significant contribution in increasing the BET surface as well as the specific capacitance of graphene. T-GR, with a capacitance of 354.1 Fg-1 at 5 mVs-1 and 264 Fg-1 at 100 mVs-1, exhibits excellent performance as a supercapacitor.